TIP60/KAT5 is required for neuronal viability in hippocampal CA1 - Urban, Inga; Zhou, Xunlei (Scientific reports, 2019)
Aberrant histone acetylation contributes to age-dependent cognitive decline and neurodegenerative diseases. We analyze the function of lysine acetyltransferase TIP60/KAT5 in neurons of the hippocampus using an inducible mouse model. TIP60-deficiency in the adult forebrain leads within days to extensive transcriptional dysfunction characterized by the presence of a neurodegeneration-related signature in CA1. Cell cycle- and immunity-related genes are upregulated while learning- and neuronal plasticity-related genes are downregulated. The dysregulated genes seen under TIP60-deficiency overlap with those in the well-characterized CK-p25 neurodegeneration model. We found that H4K12 is hypoacetylated at the transcriptional start sites of those genes whose expression is dampened in TIP60-deficient mice. Transcriptional dysregulation is followed over a period of weeks by activation of Caspase 3 and fragmentation of β-actin in CA1 neurites, eventually leading to severe neuronal loss. TIP60-deficient mice also develop mild memory impairment. These phenotypes point to a central role of TIP60 in transcriptional networks that are critical for neuronal viability.
Gesehen am 27.04.2020